TINDAK TUTUR KOMISIF DALAM SERIAL DRAMA PEAKY BLINDERS (SEASON I) - Anggraini, Melina; Rustan, Megawati; Nugroho, Miftah (TOTOBUANG, 2024)
Abstract Communication, particularly at the verbal or spoken level, demands careful attention as it has the potential to generate a multitude of interpretations from the speaker to the listener. The research focuses on identifying commissive speech acts in found in Steven Knight's drama series, Peaky Blinders. Using a qualitative descriptive method with a pragmatic approach, the research analyzes the utterances of the characters. The data for this study consists of speech acts performed by the characters in the drama series Peaky Blinders. Data collection was conducted using a note-taking and listening technique through orthographic transcription. Data analysis employed a pragmatic matching method, with the interlocutors themselves serving as the determining factor based on the speaker's language. The fundamental technique applied was the classification of determining elements. The findings reveal that speakers who make commissive utterances are accountable for their words. In this study, fifty-two patterns of commissive speech acts were identified, illustrating how language can be used to create binding commitments between speakers and their interlocutors. This study highlights the importance of considering various factors in communication, as misinterpretations can easily arise if these factors are not carefully observed. If the supportive factors of communication are not carefully observed, the chances of a misperception between the speaker and the interlocutor are greater. Ultimately, this research offers a deeper understanding of how language is employed to construct narratives and characters within a specific context, as seen in Peaky Blinders season I. Keywords: commissive speech acts, language function, Peaky Blinders   Abstrak Dalam berkomunikasi khususnya pada tataran verbal atau lisan perlu karena berpeluang untuk menghadirkan banyak persepsi dari penutur terhadap mitra tutur. Intensi focus ini adalah untuk mengidentifikasi tindak tutur komisif yang ditemukan di dalam serial drama yang berjudul Peaky Blinders karya Steven Knight. Penelitian ini menggunakan metodede deskriptif kualitatif dengan pendekatan pragmatik yang terfokus pada kajian tindak tutur. Data dalam penelitian ini berbentuk tindak tutur pada tokoh serial drama Peaky Blinders. Teknik pengumpulan data dilakukan menggunakan teknik catat dan simak melalui transkripsi ortografis. Analisis data dalam penelitian ini menerapkan metode padan pragmatik dengan alat penentunya merupakan mitra tutur itu sendiri berdasarkan bahasa penutur. Teknik dasar yang diaplikasikan ialah pilah unsur penentu (PUP). Berdasarkan hasil penelitian, dapat disimpulkan bahwa pada tindak tutur komisif, penutur harus mempertanggungjawabkan apa yang telah dituturkannya. Dalam penelitian ini ditemukan 52 tuturan yang mengandung tindak tutur komisif yang mengikat penutur terhadap tuturannya. Hal tersebut terjadi karena banyak faktor yang perlu diperhatikan dalam berkomunikasi, terutama dalam komunikasi secara verbal. Apabila faktor-faktor pendukung komunikasi tidak diperhatikan dengan saksama, peluang akan terjadinya suatu kesalahan persepsi antara penutur dan mitra tutur makin besar. Penelitian ini mampu memberikan pemahaman yang lebih mendalam tentang bagaimana bahasa digunakan untuk membangun cerita dan karakter dalam konteks tertentu, seperti yang terlihat dalam Peaky Blinders (Season I). Kata kunci: tindak tutur komisif, fungsi, Peaky Blinders